EPILEPSY WITH HETEROZYGOUS ALDH7A1 AND SLC6A1 MUTATIONS - Alili Ademi, Learta; Duma, Filip; Ademi, Blerim; Muaremoska Kanzoska, Lejla; Nonkulovski, Danilo (SHMSHM - AAMD, 2020)
ABSTRACT Epilepsy is one of the most common neurologic disorders, 75% of which begins during childhood. With the development of genetic technology, an increasing number of genes associated with epilepsy are identified. These discoveries will improve diagnosis and treatment of epilepsy and provide the basis for including genetic tests in clinical practice. We report cases of epilepsy in two sisters with heterozygous mutations in ALDH7A1 and SLC6A1 gene. Including genetic tests in the clinical practice and evaluating the results of genetic tests with the goal to better characterize the association between genes and epilepsies and to further understand the mechanisms of underlying epilepsy. The variant c.-17C>G, in 5-UTR of ALDH7A1 and c.1436G>A (p.Arg479Gln) in exon 14 of SLC6A1 gene are mutations classified as a mutations with unknown clinical meaning. The presence of variants with unknown clinical meaning should not be neglected and should not affect the clinical course and treatment.
Keywords: epilepsy; genes; ALDH7A1; SLC6A1mutation